Characterization of black crust on Pentelic and Karystos marble identification of pollution sources - Μήτσος, Δημήτριος (Πανεπιστήμιο Πελοποννήσου, 2017)
Samples of black crusts from the western facade of the Library of Hadrian (Athens) have been collected and investigated. A complete chemical and mineralogical characterization of the degradation products was conducted through optical microscopy (OM), scanning electron microscopy (SEM), X-ray fluorescence and micro X-ray fluorescence (XRF and ƒΚ-XRF), and ƒΚ-Raman spectroscopy, in order to detect pollution sources. The decay features present on the surface of the monument, consist of typical black crusts and an iron-rich aluminosilicate patina. The chemical composition of the crusts, the element distribution along the crust and the characterization of individual embedded particles could reveal groups of elements related to specific sources and related to each other. Three main typologies of particles could be identified: a) carbonaceous particles from diesel exhausts and domestic boilers, b) Si-rich particles from vehicular emissions and mineral dust, and c) metallic Ti-rich and Fe-rich particles from coal combustion and domestic heating, respectively. The main source of pollution was revealed to be traffic, with a clear fingerprint of the type and chronological development of anthropogenic pollutant deposition in the area of central Athens evident within the black crusts.
Keywords: Μαύρες κρούστες -- Διάβρωση; Μάρμαρο -- Διάβρωση; Μάρμαρο -- Ανάλυση; Μαρμάρινα κτήρια -- Ελλάδα -- Αθήνα; Αέρας -- Μόλυνση -- Φυσιολογική επίδραση -- Ελλάδα; Μνημεία -- Συντήρηση και αποκατάσταση -- Ελλάδα -- Αθήνα; Μαύρες κρούστες (black crusts); Ατμοσφαιρική ρύπανση; Αιωρούμενα αωματίδια